Pendekatan Mistisisme Dalam Pengkajian Islam - Hadi Lubis, Abdul (Al Irsyad: Jurnal Studi Islam, 2022)
Mysticism as an approach tries to see Islam from the side of the spiritual experience of a salik. The spiritual experience is in the form of encounters and revelations experienced by a creature towards the Creator. To reach this station, a seeker must first neglect several stages of purification of the soul (tazkiyatun nafs). These stages have been formulated by influential figures in the development of Sufism. The method used is qualitative with a library research approach, examining related references. As a result, the history of the development of mysticism can be divided into several periods, namely: the period in the first and second centuries, the third and fourth centuries, the fifth century, the sixth century, the seventh century, the eighth century, and the ninth century. and X and thereafter. Second, maqamat in Sufism include: al-taubah, al-zuhud, al-shabr, al-faraq, al-tawadlu, al-taqwa, al-tawakkal, al-ridla, al-ma-habbah, and al-marif, mahabbah, ma'rifat, fana' and baqa', ittihad. And unity (ittihad) can take the form of al-hulul or wahdat al-Manifestation. The three influential figures in the development of Sufism include Hasan Al-Bashri, Junaid Al-Baghdadi, Rabiatul Adawiyah, Al-Ghazali, Muhyidin Ibn Arabi, Husain bin Mansur Al-Hallaj, and so on.